Relationship Between Proficiency in Kenyan Sign Language and Signed Exact English and Performance in English by Learners with Hearing Impairment - Gregory Nyongesa (Abdul Media Literasi, 2024)
Students with Hearing Impairment (HI) encounter various challenges in learning due to their hearing loss, significantly impacting their academic performance, particularly in exams such as the Kenya Certificate of Secondary Education (KCSE). This study aims to explore the correlation between proficiency in Kenyan Sign Language (KSL) and Signed Exact English (SEE) with English performance among HI learners. Conducted in four special secondary schools for the deaf in Kenya's Nyanza region, the study involved 48 participants, including 33 Form 3 students, 7 English teachers, 4 Curriculum Support Officers, and 4 School Principals. Utilizing a qualitative multiple case study design, the research employed purposive sampling to select schools, saturated sampling for English teachers, and stratified sampling for Form 3 students. Data collection methods included in-depth interviews, focus group discussions, classroom observations, and document analysis. Thematic analysis was used to analyze the data, revealing that pre-lingual HI students, deaf before speech development, exhibit greater proficiency in KSL than SEE and Standard English (SE). Conversely, post-lingual HI students, deafened after speech acquisition, may struggle with KSL initially but tend to excel in SEE due to their prior speech development. Over time, post-lingual students may achieve proficiency in KSL after integrating into the Deaf community.